2020
DOI: 10.1111/fare.12511
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Childhood Experience With Mothers and Caregiving Outcomes in Adulthood

Abstract: Objective and Background The current study examines the types of childhood experiences with mothers (i.e., maternal abuse, affection, discipline) among caregivers of aging mothers and investigates whether membership in specific latent classes, particularly maternal maltreatment, is associated with psychological functioning among caregivers. Method Using data from the Midlife in the United States (MIDUS), we used the Bolck, Croon, and Hagenaars approach of latent class analysis to predict distal outcomes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Retrospective memories of parental affection were assessed with four items on maternal affection and one item on paternal affection. These items were adapted from the National Survey of Midlife Development in the United States (MIDUS), which was developed by Rossi (2001) and have been used to proxy parental affection in childhood (Chopik & Edelstein, 2019; Davey et al, 2009; Kong et al, 2020). The five items measured (a) whether the respondent had a good relationship with the mother before age 18, (b) how much time and attention was provided by the mother when the respondent needed it; (c) how much effort the mother put into watching over the respondent to ensure a good upbringing; (d) how much the mother taught the respondent about life; and (e) whether the respondent had a good relationship with the father before age 18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective memories of parental affection were assessed with four items on maternal affection and one item on paternal affection. These items were adapted from the National Survey of Midlife Development in the United States (MIDUS), which was developed by Rossi (2001) and have been used to proxy parental affection in childhood (Chopik & Edelstein, 2019; Davey et al, 2009; Kong et al, 2020). The five items measured (a) whether the respondent had a good relationship with the mother before age 18, (b) how much time and attention was provided by the mother when the respondent needed it; (c) how much effort the mother put into watching over the respondent to ensure a good upbringing; (d) how much the mother taught the respondent about life; and (e) whether the respondent had a good relationship with the father before age 18.…”
Section: Methodsmentioning
confidence: 99%
“…The human developmental trajectory model and life course perspective both posit that childhood experiences, especially interactions and relationships with parents, can influence life outcomes in the long run. Understanding the historical context of a person's life trajectory can deepen an understanding of their current life state (Elder et al, 2015; Kong et al, 2020). An important aspect of the parent–child relationship is parental affection, which reflects the degree of parental care and parent–child attachment in childhood (Rossi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This stepwise approach can not only provide overall significance testing of associations between latent class membership and outcomes but also perform pairwise differences testing between classes in the means of continuous outcomes (29). In addition, this method can fully consider the influence of covariates on dependent variables so that the effects of latent class membership are controlled by those covariates (30). Moreover, we used the model constraint function in Mplus to build a mediation model.…”
Section: Analytic Strategymentioning
confidence: 99%
“…The ambivalent evaluation of the relationship is also captured in a recent study of Kong et al (2020) that analyzed a sample of caregivers from the MIDUS studies. The authors identified a latent class of caregivers who each reported a contradictory experience of mothers having been both abusive and loving/affectionate during their childhood.…”
Section: Caring For a Perpetrating Parent: Caregiver Experience And Outcomesmentioning
confidence: 99%